1993
DOI: 10.1159/000182687
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Metabolic Data Following Growth Hormone Treatment of Children with Intrauterine Growth Retardation

Abstract: Twenty-five short children (6F, 19M) with intrauterine growth retardation were treated with daily subcutaneous injections of biosynthetic human growth hormone for 4 years. The treatment was commenced at a chronological age of 6.3 years (range 2.1-9.8). Eighteen of the patients had major dysmorphic signs of Russell-Silver syndrome. During the first year they were randomised into two groups treated with either 15 or 30 IU of growth hormone/m2/week. The higher dose was administered to all the children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 17 publications
6
36
0
1
Order By: Relevance
“…In the 1980s, most reports in the literature were discouraging due possibly to insufficient supplies of GH. Two recent studies, however, have shown an important catch-up growth with a mean gain in height standard deviation of 1.60 in IUGR short children following 3 years of treatment with dosages of GH approximately three times the usual replacement dose [15, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…In the 1980s, most reports in the literature were discouraging due possibly to insufficient supplies of GH. Two recent studies, however, have shown an important catch-up growth with a mean gain in height standard deviation of 1.60 in IUGR short children following 3 years of treatment with dosages of GH approximately three times the usual replacement dose [15, 16]. …”
Section: Discussionmentioning
confidence: 99%
“…Initial data were disappointing, probably due to the low dose and frequency of GH administration. Recent short term studies have shown that daily administration of recombinant human GH therapy in varying dosages accelerates growth significantly in short children born SGA (7,(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…It has been previously shown that disturbances in the GH/insulin-like growth factor I axis may account for some of the growth retardation: up to 60% of the short children born SGA have GH-secretory abnormalities and/or reduced levels of insulin-like growth factors (6 -12). Studies have shown that continuous or discontinuous treatment with recombinant human GH in varying dosages accelerates growth significantly in short children born SGA, resulting in catch-up growth to values within the normal range, followed by growth along their target height percentile (7,(13)(14)(15)(16)(17)(18)(19)(20)(21).SGA has been associated with increased prevalence of diabetes mellitus type II, hypertension, and hyperlipidemia at a relative young age in later life (22). All three disorders are risk factors of cardiovascular diseases.…”
mentioning
confidence: 99%